(untitled) (Medical Forum Monthly, 2024)
Objectives: The objective of the study was to evaluate the factors responsible for Post Graduate Resident satisfaction working in medicine, surgery and allied departments in BVH, NHM, and JHL. Study Design: Observational / Descriptive / Cross sectional study. Place and Duration of Study: This study was conducted in medicine, surgery and allied departments of BVH, NHM, and JHL from April to June 2016. Materials and Methods: A total of 210 participants took part in the study; there were 70 participants from each of the three hospitals. The sample was taken by Stratified proportionate sampling technique. The Post-Graduate Residents were given performed questionnaires to fill out. The data was analyzed by SPSS 13 and all results were presented in the form of frequencies, percentages, and tables. Results: All of the Post-Graduate Residents who were handed out the questionnaires responded, and therefore, the response rate was 100%. 77.2% of the Post-Graduate Residents were found to be neutral, while 22.8% were satisfied. Conclusions: Most of the Post-Graduate Residents were found to have a neutral response towards their professional satisfaction. The Post-Graduate Residents in BVH were more inclined towards a response of being professionally satisfied. The most popularly agreed upon workplace related factor was good working relations with colleagues.